2007
DOI: 10.1097/scs.0b013e31814e07b4
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Nasal Augmentation With Rib Cartilage Graft

Abstract: Various alloplastic and autogenous materials have been used for dorsal nasal augmentation. Bone and cartilage autografts commonly are used. We used rib cartilage graft for dorsal nasal augmentation. The aim of this study was to investigate the long-term outcomes and patient satisfaction of dorsal nasal augmentation with rib cartilage grafts. Thirty-eight patients who had been operated on for dorsal nasal augmentation with rib cartilage graft were included in this study. Operation times, postoperative complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 17 publications
2
21
1
Order By: Relevance
“…We think that any type of costal cartilage dorsal implant can result in resorption, and surgeons have to keep in mind this problem when using costal cartilage. In contrast to the current findings, Yilmaz et al 9 reported previously that the resorption rate was not high after using ACC for dorsal augmentation, and the shape of the nose had satisfactory long-term results. This discrepancy needs further clarification in future studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We think that any type of costal cartilage dorsal implant can result in resorption, and surgeons have to keep in mind this problem when using costal cartilage. In contrast to the current findings, Yilmaz et al 9 reported previously that the resorption rate was not high after using ACC for dorsal augmentation, and the shape of the nose had satisfactory long-term results. This discrepancy needs further clarification in future studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the nasal shape after dorsal augmentation using ACC, 76% of patients were reported previously as having excellent or good results. 9 Similarly, in the present study, 49 patients (71.9%) in the ACC group achieved an excellent or good result. Although, to our knowledge, the aesthetic outcomes of rhinoplasty using ePTFE have not been evaluated in previous reports, ePTFE and ACC produced similar aesthetic out- A, Excellent and poor outcomes were observed more often in the expanded polytetrafluoroethylene (ePTFE) group compared with the autologous costal cartilage (ACC) group.…”
Section: Discussionsupporting
confidence: 77%
“…This was consistent with the study by Yilmaz et al, which showed satisfactory nasal profile using rib cartilage grafts for dorsal nasal augmentation [29]. They found that the resorption rates were not high enough to change the shape of their augmented nose at 2-year follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…These studies comprised 1041 patients of whom 741 received autologous grafts and 293 received IHCC grafts. Studies were published between January 1, 1990, and December 31, 2017; the mean sample size was 36 patients (range, 9-157 patients); and studies were from countries around the world, including Turkey (n = 9), the United States (n = 5), South Korea (n = 4), Italy (n = 2), India (n = 2), the United Kingdom (n = 1), Germany (n = 1), the Netherlands (n = 1), Egypt (n = 1), South Africa (n = 1), and Saudi Arabia (n = 1) . Mean follow-up time ranged from 6 to 48 months in the studies that reported follow-up, although 8 studies did not.…”
Section: Resultsmentioning
confidence: 99%